Towards smart notifications - An adaptive approach using smart devices - López Herrera, Gustavo (2016)
The use of smart devices is increasing rapidly; this trend is changing the paradigm in which notifications are delivered to users. Smart devices are important to provide user awareness. However, their use must be controlled and human perception should be considered to avoid information overload. In this paper, we present a dynamic mechanism to coordinate the distribution of noti- fication across smart devices. This personalized notification mechanism uses an inference engine and a set of rules to generate notification alternatives and select the “best” one. A continuous refinement approach is also used to improve notification delivery. Our system was evaluated and the baseline rules were established by 11 expert users. The main results show that in some scenarios, the notification mechanism selection converged quickly and results are promising. However, further work is required to provide not only personalized but integrated (i.e., more than one device at the time) notification management.